Groundwater resources in the dry zone of Myanmar: a review of current knowledge - Pavelic, Paul; Johnston, Robyn M.; McCartney, Matthew P.; Lacombe, Guillaume; Senaratna Sellamuttu, Sonali (2018)
Groundwater resources are vital for the well-being and livelihoods of most of the ten million people living in the Dry Zone of central Myanmar. Despite this importance, there is remarkably little known or documented on the nature, extent and use of these resources. This contribution has attempted to address this gap by reviewing the literature, gathering data and stakeholder consultations. The study reveals that utilizable groundwater is present across most of the Dry Zone, most notably in the unconsolidated sedimentary aquifers that are present across large portions of the region. However, rates of replenishment appear to be relatively modest, and use is limited by high levels of salinity and arsenic that are naturally present in some areas. The scope to access groundwater is generally good, and development has steadily increased to provide water supply for domestic, agriculture and industry. In broad terms, is would appear that prospects to expand groundwater use for irrigation and other purposes are good in almost all districts. In more hydrogeologically complex settings in particular, a lack of information creates more risk that may add to drilling costs. More detailed assessments and databases are required to support effective resource management.